AB0007 Shared genetic predisposition in rheumatoid arthritis–interstitial lung disease and familial pulmonary fibrosis. (15th June 2017) - Juge, PA; Borie, R; Kannengiesser, C; Gazal, S; Revy, P; Wemeau-Stervinou, L; Debray, MP; Ottaviani, S; Marchand-Adam, S; Nathan, N; Thabut, G; Richez, C; et al.
Abstract : Background: Despite its high prevalence and mortality, little is known about the pathogenesis of RA–associated interstitial lung disease (RA-ILD). Given that familial pulmonary fibrosis (FPF) and RA–ILD frequently share the usual interstitial pneumonia pattern and common environmental risk factors, we hypothesized that the two diseases may share additional risk factors including FPF-linked genes. Objectives: Our aim was to identify coding mutations of FPF-risk genes associated with RA-ILD. Methods: We used whole-exome sequencing (WES) followed by restricted analysis of a discrete number of FPF-linked genes and performed a Burden test to assess the excess number of mutations in RA–ILD patients compared to controls. Results: Among the 101 RA–ILD patients included, 12 (11.9%) had 13 WESidentified heterozygous mutations in the TERT, RTEL1, PARN or SFTPC coding regions. The burden test, based on 81 RA–ILD patients and 1010 controls of European ancestry, revealed an excess of TERT, RTEL1, PARN or SFTPC mutations for RA–ILD patients (p=9.45'10-4, odds ratio [OR] 3.17 95% CI 1.53 – 6.12). Telomeres were shorter for RA-ILD patients with a TERT, RTEL1 or PARN mutation than controls (p=2.87x10-2). Conclusions: Our results support the contribution of FPF-linked genes to RA–ILD susceptibility. Disclosure of Interest: None declared